2020
DOI: 10.1177/2164956120907876
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Opportunity to Reflect on Experience: Interdisciplinary Mind–Body Medicine Skills Training for Health-care Professionals

Abstract: Interventions that support employee wellness and resilience hold potential to improve patient care, increase staff engagement, and decrease burnout. This repeat-measures study evaluated whether an abbreviated version of mind-body medicine skills training could decrease stress and improve mindfulness among an interdisciplinary cohort of health-care professionals. The study also assessed whether participants incorporated the mind-body medicine skills into their personal and professional lives. Aggregate results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It has been reported that diaphragmatic breathing practice improves the cognitive performance and reduces the adverse effect of stress in healthy adults [6,[14][15][16][17]. It has been provided that effective stress management strategies such as meditation, yoga, deep breathing, which is defined as a mindfulness activity efficient for integrative body-mind training and reduces stress-related disorders, contribute to healthy lifespan, increase the quality of life, and prevent sudden death [18].…”
Section: Author Detailsmentioning
confidence: 99%
“…It has been reported that diaphragmatic breathing practice improves the cognitive performance and reduces the adverse effect of stress in healthy adults [6,[14][15][16][17]. It has been provided that effective stress management strategies such as meditation, yoga, deep breathing, which is defined as a mindfulness activity efficient for integrative body-mind training and reduces stress-related disorders, contribute to healthy lifespan, increase the quality of life, and prevent sudden death [18].…”
Section: Author Detailsmentioning
confidence: 99%
“…Mindfulness activities such as reflection, sensory awareness activities, and Yoga for staff, residents, and medical students also reduce burnout at all levels of training [2][3][4]. The benefits of mindfulness and Yoga on stress management have also been demonstrated to extend broadly to nurses, teachers, police officers, and military personnel [5][6][7][8][9][10]. Unsurprisingly, mindfulness is an effective nonpharmacologic therapy for psychogenic disorders, dysthymia, and stress reduction in the general population [11][12][13].…”
Section: Introductionmentioning
confidence: 99%